Measurement of the energy asymmetry in tt[bar] j production at 13 TeV with the ATLAS experiment and interpretation in the SMEFT framework - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2022)
A measurement of the energy asymmetry in jet-associated top-quark pair production is presented using 139 fb−1 of data collected by the ATLAS detector at the Large Hadron Collider during pp collisions at √s=13 TeV. The observable measures the different probability of top and antitop quarks to have the higher energy as a function of the jet scattering angle with respect to the beam axis. The energy asymmetry is measured in the semileptonic t ̄t decay channel, and the hadronically decaying top quark must have transverse momentum above 350 GeV. The results are corrected for detector effects to particle level in three bins of the scattering angle of the associated jet. The measurement agrees with the SM prediction at next-to-leading-order accuracy in quantum chromodynamics in all three bins. In the bin with the largest expected asymmetry, where the jet is emitted perpendicular to the beam, the energy asymmetry is measured to be -0.043±0.020, in agreement with the SM prediction of -0.037±0.003. Interpreting this result in the framework of the Standard Model effective field theory (SMEFT), it is shown that the energy asymmetry is sensitive to the top-quark chirality in four-quark operators and is therefore a valuable new observable in global SMEFT fits.